2021
DOI: 10.3892/ijo.2021.5278
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and breast cancer: A way forward (Review)

Abstract: The current management of breast cancer (BC) lacks specific non-invasive biomarkers able to provide an early diagnosis of the disease. Epigenetic-sensitive signatures are influenced by environmental exposures and are mediated by direct molecular mechanisms, mainly guided by DNA methylation, which regulate the interplay between genetic and non-genetic risk factors during cancerogenesis. The inactivation of tumor suppressor genes due to promoter hypermethylation is an early event in carcinogenesis. Of note, targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Another mechanism of TAM-mediated cancer progression worth noting is via the methylation of breast cancer-specific genes to regulate gene expression [96]. A recent paper discovered that TAMs secrete IL-6 in the TME to stimulate protein arginine methyltransferase 1 (PRMT1)-mediated meR342-EZH2 formation in order to stabilize the enhancer of Zeste Homolog 2 (EZH2) in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism of TAM-mediated cancer progression worth noting is via the methylation of breast cancer-specific genes to regulate gene expression [96]. A recent paper discovered that TAMs secrete IL-6 in the TME to stimulate protein arginine methyltransferase 1 (PRMT1)-mediated meR342-EZH2 formation in order to stabilize the enhancer of Zeste Homolog 2 (EZH2) in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression is strongly influenced by DNA methylation, an epigenetic modification associated with transcriptional silencing. Tumor suppressor genes (e.g., BRCA1, ATM) are often hypermethylated in patient tumors and in peripheral blood [109,110]. Targeted and genome-wide DNA methylation studies have identified specific methylation changes associated with increased breast cancer risk and BC prognosis [111].…”
Section: Peripheral Blood Cell Transcriptome and Therapy Response And...mentioning
confidence: 99%
“…Treatment with chemotherapeutics or immunotherapy was shown to cause acquired methylation-associated resistance in cell models, and therapy resistance was also observed in BC patients [114,115]. The use of epigenetic drugs (e.g., DNMT inhibitors) is being tested in combination with chemotherapy, immunotherapy, and other treatments to overcome epigenetic alterations and treatment resistance (Figure 2) [109,116].…”
Section: Peripheral Blood Cell Transcriptome and Therapy Response And...mentioning
confidence: 99%
“…Pancreatic cancer arises in several hereditary syndromes, including Hereditary breast and ovarian cancer (HBOC), Lynch syndrome (LS), Familial atypical multiple mole melanoma (FAMMM), Familial adenomatous polyposis (FAP), Li–Fraumeni syndrome (LFS), Peutz–Jeghers syndrome (PJS), and Hereditary pancreatitis (HP) [ 5 , 6 , 7 , 8 ]. Most familial pancreatic cancer (FPC) is attributable to HBOC syndrome that results from germline mutations in BRCA1/2 genes and other genes such as ATM, BRIP1, CHEK2, RAD50 , and RAD51C [ 9 , 10 ]. In FPC belonging to HBOC, BRCA2 mutations are the most common genetic alteration, observed in about 5–10% of cases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%